Dental Metal Alloys Part 1. Classification of Dental Alloys, Physical and Chemical Properties - L. Vavřičková; T. Dostálová; D. Vahalová (Czech Dental Chamber, 2008)
Paper presented is a review of available information about physical and chemical properties of dental alloys. Their specification is also evaluated.